DEVELOPMENT OF RATE-BASED NON EQUILIBRIUM C02 REMOVAL AT ELEVATED PRESSURE FROM NATURAL GAS - ISA, FAEZAH (2016)
In this research, experimental works involving high concentration CO2 removal at elevated pressures are conducted using a high pressure CO2 pilot plant to imitate the condition at offshore platform and the result is used to validate a simulation model based on established model in literatures. Rate based non-equilibrium model using 20wt % aqueous Monoethanolamine (MEA) is developed in MATLAB based on the model of Pandya. The structure of the model includes reaction kinetics, mass transfer rate, and heat transfer and enhancement factor. Since the condition of CO2 removal at atmospheric and high pressure is different, pressure modification index-/ is experimentally derived and introduced into the original rate based non-equilibrium equations to account for the non-idealities and to reduce the prediction error between the simulation and the pilot plant data.